2007
DOI: 10.1016/j.jcf.2007.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Increased glucose excursion in cystic fibrosis and its association with a worse clinical status

Abstract: In CF, early insulin secretion defect but also IR contribute to glucose intolerance. Early in the course of the disease, increased glucose AUC and reduced early insulin secretion are more closely associated with a worse clinical status than conventional glucose tolerance categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 41 publications
2
72
1
Order By: Relevance
“…Alterations in glucose tolerance are characterized by marked glycemic peaks often followed by rapid normalization (11)(12)(13). Fasting glycemia is generally lower than in other forms of diabetes and fasting hypoglycemia has been reported (14).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in glucose tolerance are characterized by marked glycemic peaks often followed by rapid normalization (11)(12)(13). Fasting glycemia is generally lower than in other forms of diabetes and fasting hypoglycemia has been reported (14).…”
Section: Introductionmentioning
confidence: 99%
“…In the CF population, patients with and without CFRD all display significantly reduced insulin secretion [29]. There is mounting evidence that mutant CF Transmembrane Conductance regulator (CFTR), the CF disease-causing gene, is expressed in islet cells and is associated with abnormal cell function [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, other studies found no significant differences between glucose tolerance and nutrition. 1,13,34,35 In the pediatric and adult CF program at Hospital de Clínicas de Porto Alegre, patients are monitored by a nutritionist. The dietary management of CFrelated diabetes maintains a high-energy-content diet and patients are advised not to limit their intake of carbohydrates, high-fat foods, or proteins.…”
Section: Discussionmentioning
confidence: 99%
“…1 CF patients with impaired glucose tolerance have reduced pancreatic ␤ cell number and a loss of insulin secretion. 2 The prevalence of glucose intolerance in CF patients has risen in recent decades, owing to increased longevity; older individuals are more likely to have glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation